Breeding and varietal improvement of cassava in India - Nair, S.G.; Rajendran, P.G.; Naskar, S.K.; Sreekumari, M.T.; Unnikrishnan, M.; Sheela, M.N. (International Center for Tropical Agriculture, 1998)
An analysis of the recent trend in cassava area, production and yield during 1993-96 revealed an impressive increase in Tamil Nadu, which is the predominant state where cassava is grown as an industrial crop. Its present yield of 29 t/ha is the highest in the world. Even though the overall national trend in cassava area and production is declining, India's current average yield of 21 t/ha is also the world's highest.